Bilanggo life as a political prisoner in the Philippines, 1952-1962 - Pomeroy, William J. 1916- (University of the Philippines Press, 2009)
"Bilanggo is the diary of a decade behind bars. William Pomeroy and his Filipina wife Celia Mariano, like hundreds of other communists and militants, were sent to prison in the early 1950s for participating in the Huk guerilla struggle for liberation... Although this is the story of political prisoners in Philippine jails some fifty years ago, it is a story that has increasing relevance in a society that has seen increased political oppression in the last decade."--Back cover.